Polypharmacy, chronic diseases and nutritional markers in community-dwelling older - Erika Aparecida Silveira; Luana Dalastra; Valéria Pagotto (Associação Brasileira de Pós-Graduação em Saúde Coletiva, 2014)
Polypharmacy is a common practice among the elderly, but few studies have evaluated its association with nutritional markers. The aim of this study was to estimate the prevalence of polypharmacy and its association with nutritional markers, chronic diseases, sociodemographic and health variables. This research is part of the Study Elderly/Goiânia, which evaluated 418 elderly community in a cross-sectional design. Polypharmacy was defined as the use of five or more concomitant medications. The following nutritional markers were investigated: BMI, waist circumference, percentage body fat, weight gain and loss, use of diet, daily consumption of fruits, vegetables, skimmed and whole milk. Multivariate analysis was performed using hierarchical Poisson regression, with significance level set at 5%. The prevalence of polypharmacy was 28% (95%CI 23.1 - 32.5), with a significant association with feminine gender, age range 75 - 79 years, eutrophic nutritional status and obesity, use of diet, poor self-rated health and presence of two, three or more chronic diseases. The high prevalence of polypharmacy and its association with nutritional markers and chronic diseases call the attention for the need of nutritional surveillance and monitoring in the elderly.